2017
DOI: 10.16949/turkbilmat.298081
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Mathematics to Real Life: An Investigation on How Prospective Secondary Mathematics Teachers Build Real Life Connections

Abstract: Öz: Matematiğin gerçek hayatla ilişkilendirilmesi son yıllarda önemle üzerinde durulan bir konu olarak dikkat çekmektedir. Yapılan çalışmaların birçoğu bu tür ilişkilendirmelerin önemli olduğunu vurgularken, çok az bir kısmı öğretmenlerin ve öğretmen adaylarının matematiği gerçek hayatla neden ve nasıl ilişkilendirdiğini incelemektedir. Bu çalışmanın katılımcılarını, orta ölçekli bir devlet üniversitesinde matematik öğretmenliği bölümünde öğrenim görmekte olan ve 2015-2016 bahar döneminde Özel Öğretim Yöntemle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…With this feature, they can suspend students from making sense of a real-life problem. According to the literature studies supporting the findings of the first sub-purpose of the research (Altay, Erhan & Batı, 2020;Huang, 2004;Özgeldi & Osmanoğlu, 2017;Lee, 2012;Mosvold & Fauskanger, 2013;Sawyer & McDonald, 2008), the actual contexts of the activities used in mathematics teaching Inclusion alone is not enough, the real-world connections in the activity should encourage children to take higher-order thinking skills. Findings related to the second sub-purpose of the study show that in German primary school 4th-grade mathematics textbook activities, "classical verbal problems" type activities come first, "application representations of mathematical concepts" come second, and "real data analysis" activities come in third place.…”
Section: Discussionmentioning
confidence: 98%
“…With this feature, they can suspend students from making sense of a real-life problem. According to the literature studies supporting the findings of the first sub-purpose of the research (Altay, Erhan & Batı, 2020;Huang, 2004;Özgeldi & Osmanoğlu, 2017;Lee, 2012;Mosvold & Fauskanger, 2013;Sawyer & McDonald, 2008), the actual contexts of the activities used in mathematics teaching Inclusion alone is not enough, the real-world connections in the activity should encourage children to take higher-order thinking skills. Findings related to the second sub-purpose of the study show that in German primary school 4th-grade mathematics textbook activities, "classical verbal problems" type activities come first, "application representations of mathematical concepts" come second, and "real data analysis" activities come in third place.…”
Section: Discussionmentioning
confidence: 98%
“…Diğer taraftan, Yavuz-Mumcu (2018) tarafından yapılan çalışmada matematik öğretmeni adaylarının, Yorulmaz ve Çokçalışkan (2017) tarafından yapılan çalışmada ise sınıf öğretmeni adaylarının farklı disiplinler ile ilişkilendirmeye yönelik kavrayışlarının sınırlı kaldığı sonuçlarına ulaşılmıştır. Dolayısıyla, ilgili alanyazın doğrultusunda matematiksel ilişkilendirmenin genel olarak; gerçek hayatla ilişkilendirme (Boaler, 1993;Ji, 2012;Özgeldi & Osmanoğlu, 2017;Van Den Heuvel-Paunhuizen, 2003), kavramın farklı gösterimleri arasında ilişkilendirme (Ainsworth, 2008;Duncan, 2010;Özmantar ve diğ., 2010), kavramlar arası ilişkilendirme (Eli ve diğ., 2013;Narlı, 2016;Orrill & Kittleson, 2015) ve farklı disiplinlerle ilişkilendirme (Fitzallen, 2015;Honey ve diğ., 2014;Little, 2019) olarak dört ana kategori altında toplanabileceği söylenebilir. Ayrıca, bu dört ana tema bağlamında, Bingölbali ve Coşkun (2016) ilişkilendirme becerisini kuramsal bir çerçeveye oturtmuştur (Bkz.…”
Section: İlgili Literatür Ve Kuramsal çErçeveunclassified
“…Bu bağlamda, oldukça zor ve zahmetli bir süreç olmasına karşın öğretmenlerin öğretim sürecini doğru planlaması ve iyi yönetmesi dersin verimliliği açısından önem arz etmektedir (Savard & Samson, 2014). Diğer bir ifadeyle, öğrencilerin matematiği gerçek hayatla ilişkilendirmesi, öğretmenin derste bu tür ilişkilendirme kurmaya zaman ayırması ve öğrencilere bu örnekler üzerinde düşünme fırsatı vermesi ile çok yakından ilişkilidir (Özgeldi & Osmanoğlu, 2017). Dolayısıyla, öğrencilerin farklı gerçek hayat durumlarından genellemeler yaparak günlük hayattaki matematik problemlerini bulmalarına veya kurmalarına ve bu durumlar üzerinden matematiksel tartışmalar yapmalarına olanak sağlayacak çeşitli etkinlikler yapılması önemli görülmektedir (Moschkovich, 2002).…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Although PISA reports mention the difficulty of preparing second level tasks, it is stated that students should encounter such contexts as often as possible. Studies have shown that real-life situations are more motivating for students, increase students' attitudes and interest (Stylianies & Stylianides, 2008), and strengthen the connection between mathematics and daily life (Singletary, 2012;Özgeldi & Osmanoğlu, 2017).…”
Section: Introductionmentioning
confidence: 99%